#TITLE_ALTERNATIVE# - KADARISMAN (15110092) ;Dr. Ir. Kosasih Prijatna, M.Sc. , ADI
Deforestation is one of the most alarming environmental issue, mainly in tropical countries like Indonesia. An efficient method to map and monitor environmental change over time in regional scale is through remote sensing. As a tool, remote sensing provides decent coverage of both spatial and temporal aspect. Landsat is a very common satellite that often used to do mapping and monitoring task. Landsat has a 14-day temporal resolution and 30 m2 spatial resolution that covers every countries in the world. In this research, the Landsat 8 image is utilized to map forest area using Forest Canopy Density (FCD) model, a method invented by Atsushi Rikimaru. The research located in Bandung Basin in West Java Province. A Landsat 8 image from 2013 and Landsat 5 TM from 2005 located in path 122 row 65 were used as the primary data. The image then processed to become geometrically and atmospherically corrected. The USGS provided an orthorectified Landsat 7 ETM+ image to be used for geometric correction. The primary images were also went through atmospheric correction using the FLAASH module. After correction, both images processed with FCD model, resulting a map of forest canopy cover that was classified by canopy percentage. Using the processed image, the area of each forest category can be calculated, which resulted escalation during those eight years in the non-forest, medium canopy high canopy density.